(untitled) (International Journal of Nursing Education, 2020)
The research approach adopted for this study was comparative and descriptive survey. Objectives are to assess the job stress experienced by the male and female health workers. Compare the job stress of male and female health workers. Associate the job stress of male and female health workers with their selected demographic variables. A study was conducted in selected Primary Health Centre (Shanthigram, Dudda, Mosahalli, Salgama, Pension mohala) at Hassan. A sample comprised of 30 male and 30 female health workers on the alternative days the investigator selected 4 health workers by using Non-probability convenient sampling. The research design selected for the study was descriptive non-experimental design. The tool was used for the data collection was structured interview questionnaire, which has two sections. Section-A provides about socio-demographic data and section-B deals with job stress scale. The results of this study showed that the overall mean job stress score of male health workers was 27.92 with the standard deviation 23.14 and female health workers was 24.33 with the standard deviation 6.38. The overall mean job stress score of female health workers was significantly less than the male health workers. The ANOVA value was significant at p < 0.01 level showed that there was an association between satisfactions of job with the job stress male health workers. The ANOVA value was significant at p < 0.05 level showed that there was an association between leisure time activities and habitants with the job stress female health workers. There was no significant association between job stress and demographic variables like age type of family, number of children, social support, religion, additional qualification, income, working hours and year of experience.